Evaluation of the outpatient parenteral antimicrobial therapy (OPAT) service in Malaysian public hospitals: a mixed-methods study protocol - Nor Arisah Misnan; Audrey Huili Lim; Norazida Ab Rahman; Afra Nahdia Marizan Nor; Peter Seah Keng Tok (BMJ Open, 2025)
Introduction Outpatient parenteral antimicrobial therapy (OPAT) is an innovative approach to manage infections that require extended courses of intravenous antibiotics by enabling patients to receive treatment in an outpatient setting. In Malaysia, there has yet to be a systematic evaluation of the OPAT service. This study aims to describe the safety, clinical indications and treatment outcomes of the OPAT service in Malaysia, assess patients’ satisfaction and experiences and determine the facilitators and barriers associated with the provision of the OPAT service in Malaysia.Methods and analysis A mixed-methods approach combining qualitative and quantitative methods will be employed for a comprehensive understanding of the provision of the OPAT service in Malaysian public hospitals. The study consists of four distinct parts: systematic review, retrospective cohort analysis of clinical outcomes, patients’ satisfaction survey and focus group discussions on providers’ experiences. A longitudinal analysis of the clinical outcomes (treatment success/failure, infection cure, adverse events, readmission and mortality) of the OPAT patients’ cohort will be conducted using descriptive and conclusive statistics, in addition to rates of patients’ satisfaction and evaluation of providers’ experiences.Ethics and dissemination This study is registered in the National Medical Research Register (NMRR ID-24-00941-2C8) and approved by the Medical Research and Ethics Committee, Ministry of Health Malaysia (Ref: 24-00941-2C8). Written informed consent will be obtained from all participants. The results will be submitted for publication in a peer-reviewed journal and presented at one or more scientific conferences.